PENGARUH RESPONSIVENESS, TANGIBLE, DAN EMPHATY TERHADAP KEPUASAN PELAYANAN PELANGGAN PADA PT. PLN (Persero) DI KABUPATEN ENREKANG - Hamzyah Hamzyah (Jurnal Ilmu Manajemen Profitability, 2019)
Data analysis technique used in this research is multiple linear regression. To explain the description of research related to the hypothesis by using analysis: Test Validity, Test Reliability, t Test (Partial), Test F (Simultaneous). Based on the results of data analysis shows that Responsiveness (X1), Tangible (X2) and Empathy (X3), have a positive and significant effect on Customer Satisfaction (Y) shown by the value of correlation coefficient of 27.802. As for the significant test of t test that the tcount obtained is for the responsiveness variable (X1) tcount (2,212) ttable (1.98472) at 5% significance level meaning positive and significant effect on customer service satisfaction (Y), tangible tcount (6.757 ) ttabel (1,98427) at 5% significance level meaning positive and significant influence to customer service satisfaction (Y), empathy tcount (3,295) ttabel (1,98472) at 5% significance level meaning positive and significant to satisfaction customer service (Y). Tangible is the dominant variable influencing customer service satisfication based on standardized coefficients with a beta value of 0,523 or 52,3%.